A pH/ROS Cascade‐Responsive Charge‐Reversal Nanosystem with Self‐Amplified Drug Release for Synergistic Oxidation‐Chemotherapy. Issue 4 (18th December 2018) - Dai, Liangliang; Li, Xiang; Duan, Xianglong; Li, Menghuan; Niu, Peiyun; Xu, Huiyun; Cai, Kaiyong; Yang, Hui
Abstract: Poor cell uptake of drugs is one of the major challenges for anticancer therapy. Moreover, the inability to release adequate drug at tumor sites and inherent multidrug resistance (MDR) may further limit the therapeutic effect. Herein, a delivery nanosystem with a charge‐reversal capability and self‐amplifiable drug release pattern is constructed by encapsulating β‐lapachone in pH/ROS cascade‐responsive polymeric prodrug micelle. The surface charge of this micellar system would be converted from negative to positive for enhanced tumor cell uptake in response to the weakly acidic tumor microenvironment. Subsequently, the cascade‐responsive micellar system could be dissociated in a reactive oxygen species (ROS)‐rich intracellular environment, resulting in cytoplasmic release of β‐lapachone and camptothecin (CPT). Furthermore, the released β‐lapachone is capable of producing ROS under the catalysis of nicotinamide adenine dinucleotide (NAD)(P)H:quinone oxidoreductase‐1 (NQO1), which induces the self‐amplifiable disassembly of the micelles and drug release to consume adenosine triphosphate (ATP) and downregulate P‐glycoprotein (P‐gp), eventually overcoming MDR. Moreover, the excessive ROS produced from β‐lapachone could synergize with CPT and further propagate tumor cell apoptosis. The studies in vitro and in vivo consistently demonstrate that the combination of the pH‐responsive charge‐reversal, upregulation of tumoral ROS level, and self‐amplifying ROS‐responsive drug release achieves potent antitumor efficacy via the synergistic oxidation‐chemotherapy. Abstract : A cascade‐responsive micelle system with charge reversal and self‐amplifiable drug release is developed for synergistic oxidation‐chemotherapy. It activates charge reversal‐improved tumor uptake, self‐supplied tumoral reactive oxygen species (ROS) production, and self‐amplified drug release. The nanosystem significantly inhibits tumor growth and overcomes multidrug resistance (MDR) in vivo via oxidation‐chemotherapy that combines the effects of tumor acidity‐activating charge conversion and self‐amplifying ROS‐response drug release.